A role for rebinding in the prevalence of on-target side effects of clinically used antipsychotics - Sykes, David A (2020)
One explanation as to why atypical antipsychotic drugs (APDs e.g. clozapine) show reduced extrapyramidal side effects (EPS) involves their rapid dissociation from the dopamine D2 receptor (D2R). Their selective regional action in the brain permits an antipsychotic effect through inhibition of mesolimbic dopamine signalling but spares physiological dopamine neurotransmission in the striatum. This hypothesis is based largely on direct kinetic measurements using radiolabelled APDs and achieved under varied conditions and over many years. The alternative, ‘serotonin-dopamine hypothesis’ of atypicality suggests that antagonism at the 5-HT2A receptor and agonism at the 5-HT1A receptor may account for reduced EPS, due to increased nigrostriatal dopamine release. The strength of this hypothesis is currently limited to a consideration of the relative receptor affinities of APDs for the 5-HT2A and dopamine D2R, and limited data exploring their 5-HT1A agonist effects.